Adoption of diagnostic digital pathology in Finland - Juha Näpänkangas; Teemu Tolonen (Finnish Social and Health Informatics Association, 2019)
Digital pathology (DP) means digitizing histological glass slides for the assessment on a computer screen. In clinical diagnostics, DP is expected to reduce costs due to improved pathologist productivity with the aid of image analysis, workload distribution, and more accurate subspecialty-based diagnoses. The digital workflow also provides many advantages to research and education. However, the adoption of DP into clinical diagnostics has been slow. In this study, the current state and attitudes of the adoption of DP were explored with a questionnaire sent to the persons in charge of digitalization in all public pathology laboratories in Finland. Most of the respondents (75.0%) considered that there is a sufficient amount of validation studies about the safety of DP. The benefits of DP were seen in e.g. tumor boards (64.3%), logistics (64.3%), diagnostic quality (50.0%), and consultations (64.3%). All but one (92.9%) expected the level of digitalization to reach 100% in the following 12 years. The price of digitalization, specifically the cost of storage, was considered to be the most important barrier to a large-scale adoption of DP. The results suggest that there is a need for a substantial governmental financing: the virtual slide images could be stored in a central national image archive (e.g. Kvarkki) after diagnostics, leading to a remarkably reduced cost of local storage and an accelerated large-scale adoption of DP in the Finnish pathology laboratories. This would lead to improved diagnostic efficacy and quality by enabling better workload management locally and nationally. A central DP repository could serve as an invaluable database for e.g. biobank research